Stability and Vapor Pressure of Aqueous Aggregates and Aerosols Containing a Monovalent Ion - Pérez Sirkin, Yamila Anahí (2017)
The incidence of charged particles on the nucleation and the stability of aqueous aggregates and aerosols was reported more than a century ago. Many studies have been conducted ever since to characterize the stability, structure, and nucleation barrier of ion-water droplets. Most of these studies have focused on the free-energy surface as a function of cluster size, with an emphasis on the role of ionic charge and radius. This knowledge is fundamental to go beyond the rudimentary ion-induced classical nucleation theory. In the present article, we address this problem from a different perspective, by computing the vapor pressures of (H2O)nLi+ and (H2O)nCl- aggregates using molecular simulations. Our calculations shed light on the structure, the critical size, the range of stability, and the role of ion-water interactions in aqueous clusters. Moreover, they allow one to assess the accuracy of the classical thermodynamic model, highlighting its strengths and weaknesses.